Implementasi bantuan langsung tunai dana desa (BLT-DD) di desa mojoruntut kecamatan krembung sidoarjo - Sifani Maydana Pratiwi; Hendra Sukmana (STABN RADEN WIJAYA WONOGIRI, 2022)
This study aims to analyze the implementation of the Village Fund Direct Cash Assistance (BLT-DD) in Mojoruntut Village, Krembung District, Sidoarjo in line with government policies during the COVID 19 pandemic. Methodology This research is descriptive qualitative. The type of data used in this study is qualitative. Data comes from primary and secondary data through observation, interviews and documentation as data collection techniques. The implementation of the Village Fund Direct Cash Assistance (BLT-DD) is the focus of this research. The results of this study indicate that communication, in this case the village government, is the socialization of the Indonesian government program, namely BLT-DD and its acceptance criteria for Mojoruntut villagers. Resources in this case the availability of resources to support policy implementation. Mojountut village resources in this program are fully supported, especially human resources such as village heads and all village government officials and assistants who distribute BLT-DD from the center. In addition to human resources, supporting resources can come from physical facilities, infrastructure and financial resources. Regulating in this case policy enforcers, namely the government apparatus of Mojoruntut Village, Krembung District, Sidoarjo. The Mojoruntut village government runs a mechanism for distributing cash transfers directly from village funds as determined by the central government. However, when deciding Who is entitled to BLT-BD, this is an issue that needs attention. Because too many parties are trying to be selective and social jealousy. The bureaucratic structure, in this case Mojountut Village, has created a bureaucracy in the form of good coordination between agencies involved in implementing policies and managing activities, from policy formulation to practitioners in this field.